Development and validation of RP-HPLC method for estimation of Vildagliptin from table dosage form - Malakar, Aparajita; Bokshi, Bishwajit; Nasrin, Dilruba (International Journal of Pharmaceutical and Life Sciences, 2012)
A new simple, specific, precise and accurate reversed-phase liquid chromatography method has been developed for the determination of Vildagliptin (VLG) in pharmaceutical dosage form. The separation was achieved on a Xterra® Waters C18 column (150mm×4.6mm, 5?m) using mobile phase consisting of a mixture of aqueous phase (1 ml of 25% ammonium hydroxide was dissolved in 1000 ml of water for chromatography, pH of the solution was adjusted to the value of 9.5 using a 50% solution of phosphoric acid) and organic phase (methanol) in the ratio of 60:40 v/v at a flow rate of 1.0 ml/min. Detection was carried out at 210nm. The retention time of Vildagliptin was found to be 6.3 min. The calibration curve was found linear between 5- 200?g/ml (r2 = 0.9997). Limit of detection and limit of quantitation were 1.47 and 4.90 ?g/mL, respectively. The percentage recoveries of Vildagliptin were found to be in the range of 99.11-100.62%. The method was validated in accordance with International Conference on Harmonization acceptance criteria for specificity, linearity, precision, accuracy, robustness and system suitability. The excipients did not interfere in the determination of VLG. The proposed method was successfully applied for the quantitative analysis of VLG in tablet dosage form, which will help to improve quality control. DOI: http://dx.doi.org/10.3329/ijpls.v1i1.12947 International Journal of Pharmaceutical and Life Sciences Vol.1(1) 2012